Mutation spectrum of Î²-globin gene in thalassemia patients at Hasan Sadikin Hospital - West Java Indonesia - Maskoen, Ani Melani; Rahayu, Nurul S; Reniarti, Lelani; Susanah, Susi; Laksono, Bremmy; Fauziah, Prima Nanda; Zada, Almira; Hidayat, Dadang S (Cellular and Molecular Biology, 2017)
Thalassemia is the most common hereditary haemolytic anemia in Southeast Asia, in which Indonesia is among countries that are at a high risk for thalassemia. It has been reported that mutation in the beta-globin gene is responsible in severe Thalassemia. However, the spectrum of beta-globin gene mutations in Indonesian population varies in different regions . Thus, this study aimed to identify the most prevalent mutation of Thalassemia patients from the Hasan Sadikin Hospital, Bandung, using this as a reference hospital for Thalassemia in West Java. The three most prevalent mutations of beta globin (IVS1nt5, Cd26 (HbE), and IVS1nt1), were conducted in the beginning of this study. Mutations of 291 samples were detected by PCR-RFLP in the Molecular Genetic Laboratory, Faculty of Medicine Universitas Padjadjaran, Bandung. The prevalence of the beta globin gene mutation types were 47.4% IVS1nt5 homozygote, 9.9% compound heterozygote IVS1nt5/HbE, 5.4% compound heterozygote IVS1nt5/IVS1nt1, 1.4% compound heterozygote HbE/IVS1nt1, 1% HbE homozygote, 14.4% Compound heterzygote IVS1nt5/... (no paired mutation), 2.06% compound heterozygote HbE/... (no paired mutation), 1.3% compound heterozygote IVS1nt1/... (no paired mutation), and 7 samples were unidentified. The thalassemia mutation IVS1nt5 homozygote is the most common mutation found in Thalassemia patients at Hasan Sadikin Hospital, Bandung. The samples with unidentified results might carry mutations other than the three that are observed in the present study.